NASIONALISME MASYARAKAT PERBATASAN DI KALIMANTAN BARAT INDONESIA - Ully Nuzulian, Elyta, Abu Sofyan, Ishaq Rahman, (Fakultas Ilmu Sosial Ilmu Politik Pr, 2018)
Nationalism that develops in a country has various threats that are present from outside and inside, Indonesia, one of the countries that has a geographical area bordering Malaysia, needs to anticipate nationalism in the border communities so that they are not affected and tend to the progress of other countries. This study applies descriptive qualitative methods in analyzing the conditions of nationalism on the West Kalimantan border which is focused on the Sajingan Besar border area. The results of the study on the Sajingan Besar Sambas region showed two results from the point of view of nationalism conditions which refer to nationalism indicators, namely: (1). National identity, (2). The role of government in increasing national awareness; (1). The identity of the Sajingan Besar border community, based on awareness, identity and national ideology of the border communities where border communities depend on Malaysia and require access in and out of the country and can lead to multiple identities until citizenship is moved because of the weak development of the border region potentially weakening nationalism; (2). The role of the government in increasing national awareness, the dependence of border communities is due to weak development while the Malaysian border is already fairly developed which can affect border community nationalism which will tend to development in Malaysia.Â